Hidrolisis Minyak Sawit : Katalitik dan Non Katalitik. - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2005)
The effects of temperature and catalyst concentration on reaction rate of palm oil hydrolyzed with and without catalyst have been studied The catalytic and non catalytic hydrolyses were, respectively, performed in a three neck flask and an autoclave. The volumetric ratio of reactants, oil to water, was kept constant. Within the limited range of experimental conditions, the evaluated rate constant of palm oil catalytic (sulfuric acid) hydrolyzed, by assuming the system was homogeneous, was found that { 75963 _2.376c k =1.445x108 e RT ) ki with average deviation 14.3 %. The rate constant for non catalytic 4133606) was equal to k = 1.3 lx1013e RT ill with average deviation 12.9 %. A suitable catalyst was needed in order to hydrolyze palm oil at lower than 513 K Sulfuric acid catalyst lowered 50 % the activation energy of non catalytic hydrolysis.